2015
DOI: 10.2217/epi.15.101
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Growth Restriction and Methylation of Growth-Related Genes in the Placenta

Abstract: Aim:To examine the associations between fetal growth restriction (FGR) and DNA methylation of six growth-related genes in human placenta. Materials & methods: A total of 181 mother-newborn pairs (80 FGR cases and 101 controls) were enrolled in this case-control study. Placental DNA methylation was measured by bisulfite pyrosequencing. Results: DNA methylation levels of IGF2 and AHRR were positively associated with newborn birth weight and Quetelet's index, while DNA methylation levels of HSD11B2 and WNT2 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Epigenetics (Xiao et al, 2016) and gene expression (Buffat et al, 2007;Madeleneau et al, 2015) reprogramming play a central role in IUGR. However, the pathophysiological connections between these two fields of high-throughput analyses have only recently begun to be studied (Ding and Cui, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetics (Xiao et al, 2016) and gene expression (Buffat et al, 2007;Madeleneau et al, 2015) reprogramming play a central role in IUGR. However, the pathophysiological connections between these two fields of high-throughput analyses have only recently begun to be studied (Ding and Cui, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as having a weight at two standard deviations (tenth percentile) below that of a normal fetus, or at <2.5 kg after 37 weeks of pregnancy (Seravalli and Baschat, 2015). The cause for abnormal fetal size may be either extrinsic (placenta, matrix) or intrinsic to the fetus itself (Lewis et al, 2016;Xiao et al, 2016). Studies have shown that FGR is the second leading cause of deaths among fetuses during the perinatal period, with a threefold increase in mortality rates as compared to that of a normal neonate (Boulet et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ performed in rather small scale settings, and were more focused on intrauterine growth restriction (IUGR) or SGA birth outcomes [30][31][32][33] . Bourque et al, using 35 placenta samples, showed no difference in LINE-1 methylation comparing intrauterine growth restricted newborns to newborns with normal birth weight 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, investigating DNA methylation levels on a global scale might facilitate getting first insights into epigenetic mechanisms of complex phenotypes 28,29 . However, studies investigating correlations between global DNA methylation and birth weight so far were only performed using rather small sample sizes [30][31][32][33] .…”
mentioning
confidence: 99%